Experimental investigation of flameless combustion of biodiesel - Orati, Edson [UNESP]; Veríssimo, Anton S. [UNESP]; Rocha, Ana Maura A.; Costa, Fernando S.; Carvalho, João A. [UNESP] (Elsevier, 2022)
A laboratory-scale combustor was investigated under flameless biodiesel combustion. The biofuel was used due to its importance as a green fuel substitute for conventional fossil diesel, in order to reduce the emission of greenhouse gases. The combustor design was based on the phenomenon of internal recirculation, whose intensity is determined by the airflow jet momentum rate through its air intake nozzle. This investigation is important to identify the physicochemical phenomena that govern flameless combustion of liquid fuels, in addition to determining the operating parameters of the burner. A pressure swirl atomizer was used to atomize the biodiesel. The influence of biodiesel temperature and pressure on the droplet size was investigated. Results show that after a certain liquid pressure and preheating temperature, the droplet size does not vary. The combustor aerodynamics promoted adequate mixing of fuel vapor in the vicinity of the droplet interface with diluted oxidant, as a result of high airstream jet momentum rate, leading to distributed combustion reactions. The experimental results showed that combustion at high rates of excess air and preheated air fulfilled the typical characteristics of flameless combustion due to the indistinguishable flame limits, reduced combustion noise levels, absence of soot emissions and low emissions of NOx and CO, simultaneously. On the other hand, combustion in low excess air resulted in the stabilization of a bright yellowish flame with high soot emissions together with a sharp increase in CO emissions. The droplet size has a significant influence on the establishment of stable combustion. For droplet sizes above 35 μm it was impossible to keep the burning of the biodiesel. NOx and CO emissions were affected by the excess air and temperature variations.
Keywords: Biodiesel; Biofuel; Flameless combustion; Pollutants emissions; Pressure-swirl atomizers